(untitled) (gjstudies, 2022)
This research examines the effectiveness of post-incident audit reviews in banking institutions following cyber and financial fraud incidents, with particular focuson how these reviews contribute to improved internal control frameworks. Throughcomprehensive analysis of 147 documented fraud cases across global financial institutions from 2019 to 2022, this study develops a systematic framework for evaluating post-incident learning and control enhancement. The research introduces anovel Post-Incident Improvement Index (PIII) that quantifies control framework enhancements across technological, procedural, and organizational dimensions. Empirical results demonstrate that institutions conducting rigorous post-incident audits achieve 58% greater control improvements and 42% faster implementation ofcorrective measures compared to those with less systematic review processes. Thestudy reveals that cyber fraud incidents predominantly drive technological controlenhancements, while financial fraud cases more significantly influence proceduraland organizational controls. Findings indicate that successful post-incident learning requires structured review methodologies, cross-functional collaboration, andsystematic knowledge retention mechanisms. This research contributes both theoretical advancements in organizational learning from security incidents and prac-tical implementation guidelines for banking institutions seeking to enhance theirresilience through systematic post-incident analysis and control framework evolution.